Rural roads infrastructure and women empowerment in India - Bharti Nandwani; Punarjit Roychowdhury (Global Labor Organization (GLO), 2023)
The paper examines the impact of a rural roads construction program in India on women's outcomes. While spatial integration can provide women with increased education and employment opportunities, the extent of benefits might be limited by underlying gender norms. We identify the impact of the policy by exploiting the program rule that assigned roads based on the village population. Using a two-way fixed effect methodology, we find that increase in rural roads construction lowers mobility restrictions faced by women and improves norms around domestic violence. However, the result are mixed with respect to participation in other decision making and financial autonomy. Additionally, while we find positive impact on education, there is no impact on employment outcomes for females. We argue that a possible reason for a partial improvement in women outcomes could be gendered impact of the policy - men benefit more in terms of employment than women.
Keywords: J16; O12; 330; Gender Norms; India; Roads; Women Empowerment